LEADING INDIAN BUSINESS-GROUPS - M. A. Vorobyeva (Vestnik MGIMO-Universiteta)
The goal of this paper is to investigate the evolution of the leading Indian business-groups under the conditions of economical liberalization. It is shown that the role of modern business-groups in the Indian economy is determined by their high rate in the gross domestic product (GDP), huge overall actives, substantial pert in the e[port of goods and services, as well as by their activities in modern branch structure formatting, and developing labor-intensive and high-tech branches. They strongly influence upon economical national strategies, they became a locomotive of internationalization and of transnationalization of India, the basis of the external economy factor system, the promoters of Indian "economical miracle" on the world scene, and the dynamical segment of economical and social development of modern India. The tendencies of the development of the leading Indian business groups are: gradual concentration of production in few clue sectors, "horizontal" structure, incorporation of the enterprises into joint-stock structure, attraction of hired top-managers and transnationaliziation. But against this background the leading Indian business-groups keep main traditional peculiarities: they mostly still belong to the families of their founders, even today they observe caste or communal relations which are the basis of their non-formal backbone tides, they still remain highly diversificated structures with weak interrelations. Specific national ambivalence and combination of traditions and innovations of the leading Indian business-groups provide their high vitality and stability in the controversial, multiform, overloaded with caste and confessional remains Indian reality. We conclude that in contrast to the dominant opinion transformation of these groups into multisectoral corporations of the western type is far from completion, and in the nearest perspective they will still possess all their peculiarities and incident social and economical "colouring".